Sex‐dependent long‐term effects of adolescent exposure to THC and/or MDMA on neuroinflammation and serotoninergic and cannabinoid systems in rats. (March 2014) - Lopez‐Rodriguez, Ana Belen; Llorente‐Berzal, Alvaro; Garcia‐Segura, Luis M; Viveros, Maria‐Paz
<x xml:space="preserve">Abstract</x> Background and Purpose Many young people consume ecstasy as a recreational drug and often in combination with cannabis. In this study, we aimed to mimic human consumption patterns and investigated, in male and female animals, the long‐term effects of Δ9‐tetrahydrocannabinol (THC) and 3, 4‐methylenedioxymethamphetamine (MDMA) on diverse neuroinflammation and neurotoxic markers. Experimental Approach Male and female Wistar rats were chronically treated with increasing doses of THC and/or MDMA during adolescence. The effects of THC and/or MDMA on glial reactivity and on serotoninergic and cannabinoid systems were assessed by immunohistochemistry in the hippocampus and parietal cortex. Key Results THC increased the area staining for glial fibrilar acidic protein in both sexes. In males, both drugs, either separately or in combination, increased the proportion of reactive microglia cells [ionized calcium binding adaptor molecule 1 (Iba‐1)]. In contrast, in females, each drug, administered alone, decreased of this proportion, whereas the combination of both drugs resulted in a 'normalization' to control values. In males, MDMA reduced the number of SERT positive fibres, THC induced the opposite effect and the group receiving both drugs did not significantly differ from the controls. In females, MDMA reduced the number of SERT positive fibres and the combination of both drugs counteracted this effect. THC also reduced immunostaining for CB1 receptors in females and this effect was aggravated by the combination with MDMA. Conclusions and Implications Adolescent exposure of rats to THC and/or MDMA induced long‐term, sex‐dependent neurochemical and glial alterations, and revealed interactions between the two drugs. Linked Articles This article is part of a themed section on Cannabinoids 2013. To view the other articles in this section visit http://dx.doi.org/10.1111/bph.2014.171.issue‐6